2020
DOI: 10.3892/ol.2020.11777
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of fibrin sealant as a hemostatic technique in accelerating endoscopic submucosal dissection-induced ulcer healing and preventing stricture in the esophagus: A retrospective study

Abstract: The aim of the present retrospective study was to evaluate the effectiveness of conservative electrocoagulation followed by porcine fibrin sealant (FS) as a protective hemostatic technique for wounded microvessels in promoting the healing of endoscopic submucosal dissection (ESD)-induced ulcer, and preventing esophageal strictures that follow ESD. A total of 203 patients with early esophageal cancer or precancerous lesions were retrospectively analyzed. The 1-month ulcer healing and stricture rates were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…We did not perform prophylactic coagulation on nonbleeding visible vessels smaller than 0.3 mm in the post-ESD ulcer. Our previous study showed that a wound microvessel-protective hemostatic technique followed by porcine fibrin sealant can promote ESD-induced ulcer healing without increasing delayed bleeding events[ 15 ]. Prophylactic hemostasis-induced tissue damage or necrosis may lead to the exposure of arteries on the base of the ulcer, which in turn would contribute to delayed episodes of bleeding[ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…We did not perform prophylactic coagulation on nonbleeding visible vessels smaller than 0.3 mm in the post-ESD ulcer. Our previous study showed that a wound microvessel-protective hemostatic technique followed by porcine fibrin sealant can promote ESD-induced ulcer healing without increasing delayed bleeding events[ 15 ]. Prophylactic hemostasis-induced tissue damage or necrosis may lead to the exposure of arteries on the base of the ulcer, which in turn would contribute to delayed episodes of bleeding[ 21 ].…”
Section: Discussionmentioning
confidence: 99%